Penerapan Model Pembelajaran Learning Cycle 7e untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Nur Efendi; Dian Nur Mufidah (SEJ (Science Education Journal), 2018)
The purpose of this study was to analyze students' critical thinking skills through the application of learning cycle type 7E at SMPN 1 Krembung. This research is a quan- titative research type of quasi-experiment with one-group pretest-posttest design. Data were collected using pretest and posttest to measure students' critical thinking skills with critical thinking indicators from Robert H. Ennis. Data were then analyzed using N-Gain to determine the improvement of students' critical thinking skills. The results showed that the indicator of critical thinking skills "determines actions" gained the highest N-gain score of 0.8 and the lowest N-gain value is the "focus question" indicator of 0.167.